2013
DOI: 10.1021/ie401470w
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Coconut Milk Processing Waste as a Low-Cost Mercury Sorbent

Abstract: Desiccated coconut waste sorbent (DCWS), a byproduct of coconut milk processing, was studied as a sorbent for Hg(II) sorption. Energy dispersive X-ray analysis indicated that the DCWS mainly contained C, N, and O, while the Fourier transform infrared measurements confirmed the existence of hydroxyl, carboxyl, and amine groups on the DCWS surface. The point of zero charge (pH pzc ) and cation-exchange capacity (CEC) values were 6.05 and 2.02 meq/100g, respectively. The batch equilibrium data were fitted well by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 56 publications
4
29
0
1
Order By: Relevance
“…The rate of increase under highly acidic conditions (pH 2–4) was mostly higher than that observed at milder acidic conditions (pH 4–6) [6, 72, 84, 100102, 104, 108, 125, 129, 130]. Under basic conditions (pH > 7), heavy metal uptake decreased with pH [100, 101, 108]. Under severe acidic conditions, the very low reported uptake capacities were attributed to the fact that H + ions compete with the metal ions on the active sites [72, 101, 126] which indicates that biosorption is governed by electrostatic interactions under these conditions.…”
Section: Operating Factors Influencing Biosorptionmentioning
confidence: 99%
See 3 more Smart Citations
“…The rate of increase under highly acidic conditions (pH 2–4) was mostly higher than that observed at milder acidic conditions (pH 4–6) [6, 72, 84, 100102, 104, 108, 125, 129, 130]. Under basic conditions (pH > 7), heavy metal uptake decreased with pH [100, 101, 108]. Under severe acidic conditions, the very low reported uptake capacities were attributed to the fact that H + ions compete with the metal ions on the active sites [72, 101, 126] which indicates that biosorption is governed by electrostatic interactions under these conditions.…”
Section: Operating Factors Influencing Biosorptionmentioning
confidence: 99%
“…For heavy metal sorption, it was found that the increase in pH increases uptake capacity of heavy metals such as Cd, Pb, Ni, Cu, and Zn in both the acidic and the neutral range (pH 2–7). The rate of increase under highly acidic conditions (pH 2–4) was mostly higher than that observed at milder acidic conditions (pH 4–6) [6, 72, 84, 100102, 104, 108, 125, 129, 130]. Under basic conditions (pH > 7), heavy metal uptake decreased with pH [100, 101, 108].…”
Section: Operating Factors Influencing Biosorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomaterials such as bacteria, fungi, algae, industrial wastes (e.g., food/beverage wastes, fermented wastes, anaerobic sludge, and activated sludge), agricultural wastes (e.g., fruit/vegetable wastes, rice residues, and palm oil residues), and natural residues (e.g., plant residues, saw dust, and tree bark) have been widely studied as biosorbents to treat wastewater containing organic and inorganic pollutants such as dyes, antibiotics, pesticides, and heavy metals Bhatnagar and Sillanpaa 2010;Demirbas 2008;Hasfalina et al 2010;Johari et al 2013;Macías-García et al 2012;Park et al 2010;Song et al 2013). The use of agricultural residues as alternative biosorbents for replacing the conventional adsorbents has also been widely studied.…”
Section: Introductionmentioning
confidence: 99%